2004
DOI: 10.4049/jimmunol.173.11.6735
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Macrophage-Mediated HIV-1 Induction

Abstract: Viral latency is a long-term pathogenic condition in patients infected with HIV-1. Low but sustained virus replication in chronically infected cells can be activated by stimulation with proinflammatory cytokines such as TNF-α, IL-1 β, or other host factors. However, the precise mechanism by which cellular activation induces latently infected cells to produce virions has remained unclear. In the present report, we present evidence that activation of HIV-1 replication in latently infected U1 or ACH2 cells by hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 64 publications
0
41
0
Order By: Relevance
“…Normally, the activation of TLRs in monocytes/macrophages by bacteria leads to the production of proinflammatory cytokines (e.g., TNF-␣, IL-1␤, and IL-6). Importantly, these proinflammatory cytokines have been suggested as an important mechanism of HIV-1 reactivation in latently infected cells (20,61). Hence, to test whether production of these cytokines in response to F. nucleatum and P. gingivalis was playing a role in HIV-1 promoter activation, we first determined the levels of TNF-␣, IL-1␤, and IL-6 produced by either THP89GFP cells or their parental THP-1 cells in response to different concentrations of bacterial extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, the activation of TLRs in monocytes/macrophages by bacteria leads to the production of proinflammatory cytokines (e.g., TNF-␣, IL-1␤, and IL-6). Importantly, these proinflammatory cytokines have been suggested as an important mechanism of HIV-1 reactivation in latently infected cells (20,61). Hence, to test whether production of these cytokines in response to F. nucleatum and P. gingivalis was playing a role in HIV-1 promoter activation, we first determined the levels of TNF-␣, IL-1␤, and IL-6 produced by either THP89GFP cells or their parental THP-1 cells in response to different concentrations of bacterial extracts.…”
Section: Resultsmentioning
confidence: 99%
“…6C) (mean concentrations of Ͼ10 pg/ml) revealed that MEC are highly secretory cells that release a variety of immune mediators with widely ranging concentrations. Several of these factors, including IL-8 and IL-6, have been shown to upregulate HIV-1 replication in vitro (7,12,20) and may contribute to the observed increase in virus replication in PBMCs exposed to MEC secretions.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the apical secretions from the polarized cells by multiplex assays revealed the presence of a complex array of cytokines, chemokines, and growth factors. Breast milk is known to contain many chemokines and cytokines (24,41), some of which may influence HIV-1 infection and transmission (7,12,20). Epidemiologic studies have sought to find correlations between individual breast milk components and transmission of HIV-1 through breast-feeding or between HIV-infected and noninfected women (8,35,42,44).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that stimulation of viral replication in chronically infected cells is due to activation of NF-B. In addition to IL-1 and TNF-, contact with macrophages as well as a number of stressors can stimulate NF-B, including phorbol esters, radical oxygen intermediates, and UV irradiation (Devadas et al;. Clinical manifestations of AIDS include both immunologic and neurologic disorders.…”
Section: Interleukin 1 (Il-1) and Hiv Infectionmentioning
confidence: 99%
“…Chronic infection and viral latency are typical of HIV-1 infection. Stimulation with IL-1 as well as TNF-can stimulate viral replication in chronically infected cells (Devadas et al;. Monocytes are also major reservoirs for HIV-1 in infected tissue and vectors for virus transmission to target cells, as well as sources of potent cytokines that can affect cell function and virus replication (Devadas et al;.…”
Section: Interleukin 1 (Il-1) and Hiv Infectionmentioning
confidence: 99%